2016
DOI: 10.1016/j.chemosphere.2016.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and photocatalytic application of TiO2/Fe-ZSM-5 nanocomposite for the treatment of petroleum refinery wastewater: Optimization of process parameters by response surface methodology

Abstract: Photocatalytic degradation of organic contaminants from petroleum refinery wastewater under UV and sunlight was investigated by immobilizing nanosized TiO2 photocatalyst into the structure of as-synthesized Fe-ZSM-5 zeolite via sol-gel method. Pure phase of TiO2/Fe-ZSM-5 photocatalyst with specific surface area of 304.6 m(2) g(-1) and loaded TiO2 of 29.28% was successfully synthesized. Effects of various operational parameters on treatment process were investigated by use of Response Surface Methodology (RSM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…In this process, pH was a key operational parameter. Fe-based catalyst could possess a high activity at pH 6-9 [74][75][76]. On the contrary, at pH 6, many molecular ozone and little CO 3 2− existed in the weakly acidic solution, which led to better COD removal.…”
Section: Iron Oxidesmentioning
confidence: 99%
“…In this process, pH was a key operational parameter. Fe-based catalyst could possess a high activity at pH 6-9 [74][75][76]. On the contrary, at pH 6, many molecular ozone and little CO 3 2− existed in the weakly acidic solution, which led to better COD removal.…”
Section: Iron Oxidesmentioning
confidence: 99%
“…The above photocatalytic reaction mechanism indicates that the degradation method is a clean technology and can be applied to the treatment of several wastewater applications where unwanted organics may exist [12]. Similar thoughts are shared by Ghasemi et al [13], where it was reported that some of the key benefits of using TiO 2 for PCD include the fact that no sludge formation occurs in the complete elimination of the contaminants. In addition, the use of the TiO 2 particles due to its ability to remove organics and in some cases inorganic pollutants, makes it appealing.…”
Section: Introductionmentioning
confidence: 58%
“…The PCD, as one of the emerging techniques, has some setbacks in operations which affects the TiO 2 reaction rate, hence requires an optimized condition to enhance effective degradation of the contaminants [8,11]. Some of the main factors that can affect the performance of PCD with TiO 2 include photo catalyst concentration, pH of the solution, reaction temperature, concentration of the pollutants, presence of inorganic ions, flow rate of air sparged, light intensity or wavelength and reaction time [13].…”
Section: Introductionmentioning
confidence: 99%
“…Eq. (1) was applied to explain the effect of independent variables in the second-order polynomial model: (1) where Y is the response (effi ciency removal), a 0 is the intercept value, a i , a ii , and a ij are regression coeffi cients, x i and x j are the independent variables, and e is the random error 9 . Analysis of variance was used to fi nd the interaction between the independent variables and the response.…”
Section: Experimental Design and Variablesmentioning
confidence: 99%